Study of some biological characteristics of hydatid cysts in sheep in al-Shuula area in Baghdad - YOUNIS, KHALIDA HUSSAIN (The Iraqi Journal of Veterinary Medicine, 2011)
The study was implemented to identify some the biological characteristics of 2428 hydatid cysts in 353 naturally infected animals out of 2781 slaughtered sheep in al-Shuula area in Baghdad. The results revealed that 1669 cysts in 211 infected females and 759 cysts were presence 142infected males. The diameter of hydatid cysts varies from 0.1-16.4 cm . The surrounding cysts were larger than the cysts in the center of the infected organ with multiple cysts. The cysts were unilocular rounded. and mostly found in infected livers. They were few cysts with free fertile or sterile daughter cysts. The hydatid liquid was clear for most hydatid cysts. and its volume was ranged between (0.2-930) ml. The protoscolises were found white in color and their number were ranged between 4322.8±127.8 in male`s livers and9472.5 ±432.5 in female`s livers. The bio-activity of hydatid cysts reached with an average 73.32% and 89.3% in livers . The fertility percentage of the cysts was 60.25 %. and it was higher in females than in males. The study also revealed that such percentage in infected livers was higher than that of infected lungs and that of the second aged group ( two _ less than four years ) for both animals sexes . The results of the present study indicate no relation among diameter of hydatid cysts. quantity of protoscolises inside the cysts. fertility and viability of protoscolises.